Assembleia de aves registradas em armadilhas fotográficas na flona de Caxiuanã - CARDOSO, Douglas Nascimento (2024)
The article aims to determine the bird species recorded from camera traps in the Caxiuanã National Forest, since studies of the Amazon bird fauna are extremely important to understand their diversity, and can be the basis for subsequent studies. The study was developed based on data collected between 2010 and 2017, provided from capture by camera traps. 1242 bird detections were made, in which 7 orders, 7 families, 11 genera and 14 species were identified. Cameras as a method for data collection proved to be important tools in monitoring some terrestrial bird communities, where greater abundance stood out in the records of guilds of Frugivorous and Omnivorous birds in the litter and understory. There was a difference in the composition of the birds in relation to the two banks of the Caxiuanã River, the difference in the record may have influenced the river's influence on the distribution of the birds.